Мужские сексуальные тайны - Еникеева Диля Дэрдовна (Откровенно о сокровенном, 2003)
Экземпляры: ф.6 (20171226) / Инвентарный номер: 2113 / Цена: / Сис.шифр: 88.37 / Авт.знак: Е 63 / ГРНТИ: 15.41.49 / ББК: 88.37